ZNF561-AS1 Regulates Cell Proliferation and Apoptosis in Myocardial Infarction Through miR-223-3p/NLRP3 Axis. (August 2022) - Li, Xiaoyu; Long, Jun; Zong, Ligeng; Zhang, Chengcheng; Yang, Zhongxin; Guo, Shengnan
Long non-coding RNAs (lncRNAs) have been widely recognized as important regulators in myocardial infarction (MI) and other heart diseases. Our study aimed to investigate the mechanism and biological function of an unknown lncRNA zinc finger protein 561 antisense RNA 1 (ZNF561-AS1) in MI. After confirming the MI model was successful, we applied reverse transcription quantitative polymerase chain reaction and Western blot (WB) and found that the expression of NLR family pyrin domain containing 3 (NLRP3), interleukin (IL)-1β, and IL-18 was substantially increased in infarct and border zones of MI mice heart at 24 h and 72 h compared with that in sham-operated models. Moreover, we found that NLRP3 expression was promoted in hypoxia human cardiomyocytes (HCMs). Through cell function assays including CCK-8, 5-Ethynyl-2'-deoxyuridine (EdU), flow cytometry, and TdT-mediated dUTP Nick-End Labeling (TUNEL), supported by WB analysis, we verified that silencing of NLRP3 facilitated proliferation but impeded apoptosis of hypoxia-induced myocardial cell. Moreover, Ago2-RIP and RNA pull-down assays displayed that NLRP3 could combine with miR-223-3p. Luciferase reporter assays further confirmed that NLRP3 was directly targeted by miR-223-3p. Simultaneously, we found that miR-223-3p was the downstream gene of ZNF561-AS1. In addition, we conducted a series of rescue experiments to affirm that ZNF561-AS1 regulated cell proliferation and apoptosis in MI through miR-223-3p/NLRP3 axis.